Tropical Residual Soil Properties on Slopes - Mohd Fakhrurrazi, Ishak; Muhammad Farhan, Zolkepli; Mohammad Affendy, Omardin (Penerbit Universiti Malaysia Pahang, 2017)
Tropical residual soil is a product of chemical weathering, thus its characteristics are dependent upon environmental factors such as parent rocks, climate, topography and age. This type of soil can be found in many countries all over the world, especially in the tropical region. Since there are many accident happens due to slope failure, a comprehensive laboratory study need to be conducted in order to determine the properties of soil located at Pahang Matriculation College. Several experiments involving physical index and engineering properties of soil are conducted. The typical tropical residual properties are showed and can be considered as sandy SILT of high plasticity.